A safe haven in times of crisis: The appeal of family companies as employers amid the COVID-19 pandemic. Issue 1 (March 2023) - Jaufenthaler, Philipp
Abstract: Family firms often struggle to recruit skilled non-family employees. Applying a mixed-method strategy, this article investigates the changing perception of family firms as attractive employers in the context of the COVID-19 pandemic. Experimental results indicate that family firms benefit from a greater popularity amid crises owing to perceptions that they offer greater job security and compensation. Qualitative findings expand on these results by identifying new attractiveness-relevant factors that only come into play amid crises—specifically, multifaceted conceptions of family firms' crisis responses and their importance for local communities and economies contribute to their situational appeal. Highlights: Signaling family business enhances the attractiveness of employers amid COVID-19. A mixed-methods design offers a nuanced look into family firms' appeal amid crises. Expectations of family firms' crisis response mainly account for the situational appeal. Another contributor is the perceived local importance of family firms amid crises. A field study supports the findings of the lab experiment.